Nuptial Rape: Rape Within Marriage (Indian Journal of Social Science and Literature (IJSSL), 2024)
Section 375 of the Indian Penal Code, 1860 Criminalizes ’Rape’ under Offences Affecting the Human Body, where prevails an oddly fitted exception to this Section, which states: Sexual intercourse by a man with his wife who is not less than 15 years of age does not amount to the offence of rape. Marital Rape, a non-criminalized crime in India is where the victim herself does not know she is a victim of Marital Rape. It is one of the most under-reported crimes with 77% of women never seeking any aid regarding the violence they ever experienced. The section clearly states that rape within marriage cannot be treated as a criminal offence unless the wife is below 15 years of age. Considering the repercussions, the adverse effect on mental health highly caused by marital rape due to its non-criminalization, especially in India is reviewed legally and psychologically in this paper. The data for the above piece of research has been taken from Secondary sources: law sites, search engines, research articles, Google Scholar etc.